Maternal depression and loss of children under the one-child family planning policy in China: a cross-sectional study of 300 000 women - Kun Tang; Hanyu Wang; Tong Xin; Eric Frasco; Jie Shang; Minne Chen (BMJ Open)
Objectives This study aims to explore the association between maternal depression and the loss of the only child under the family-planning (FP) policy.Design Cross-sectional data from a Chinese population-based study were analysed.Setting Population from 10 (5 rural and 5 urban) areas in China.Participants Around 300 000 females were included in the study. The FP group was defined as women with one or two live births. Those with no surviving child were classified into the loss-of-only-child group. The non-FP group included women who had more than two live births. Logistic regression was used to assess the relationship between major depressive disorder (MDD) and family types, after stratification and adjustment.Outcome MDD was assessed using the Composite International Diagnostic Inventory.Results The odds of MDD are 1.42 times higher in the FP group in general (OR=1.42, 95% CI: 1.28 to 1.57), as opposed to the non-FP group. In particular, the odds of MDD are 1.36 times greater in the non-loss-of-only-child group (OR=1.36, 95% CI: 1.21 to 1.51) and 2.80 (OR=2.80, 95% CI: 0.88 to 8.94) times greater in the loss-of-only-child group, compared with the non-FP group. The associations between FP groups and MDD appeared to be stronger in the elderly population, in those who were married, less educated and those with a higher household income. The association was found progressively stronger in those who lost their only child.Conclusions People in the FP group, especially those who lost their only child, are more susceptible to MDD than their counterparts in the non-FP group. Mental health programmes should give special care to those who lost their only child and take existing social policies and norms, such as FP policies, into consideration.